Final year undergraduate nursing and midwifery students' perspectives on simulation-based education: a cross-sectional study - Mairead Moloney; Louise Murphy; Liz Kingston; Kathleen Markey; Therese Hennessy; Pauline Meskell; Sandra Atkinson; Owen Doody (BMC, 2022)
Abstract Background Simulation-based education is a teaching and learning approach that can enhance learning experiences for students on healthcare programmes. Within undergraduate nursing and midwifery education, simulation can support students in developing graduate attributes necessary to become practice-ready professionals. This paper reports on the evaluation of a simulation-based education initiative, which was introduced to support final year undergraduate nursing and midwifery students in preparation for their upcoming clinical internship in practice. Methods This study aimed to evaluate a simulation-based education initiative from the perspectives of final year undergraduate nursing and midwifery students (N = 95). An online survey, using the validated Simulation Effectiveness Tool - Modified (SET-M), was distributed to final year nursing and midwifery students at one university in Ireland. This study was conducted and reported in line with the Consensus-Based Checklist for Reporting of Survey Studies (CROSS). Results The results of the study highlight final year nursing and midwifery students' perceptions, experiences, and satisfaction with learning in a simulated environment. Students reported their simulation-based learning experiences as worthwhile, motivating, and as important opportunities to build on previous learning, increase confidence and gain experience in preparation for real-life practice. Students reported feeling more confident in their assessment skills, in providing care and interventions in responding to changes in a person's health status. All students reported that the simulation-based learning experiences enabled them to think more critically about the clinical case scenarios and critically question their actions and decision-making processes. Pre-briefing and debriefing sessions were highlighted as important aspects of the simulation which helped to increase student confidence and cultivate meaningful learning. Conclusion Simulation-based education is a valuable teaching and learning modality, particularly for final year students who are transitioning to real-life clinical practice. Student-centred simulation-based learning experiences can cultivate professional development and support learners in their transition from university student to healthcare professional.